A Model of Transportation of Sterile Medical Supplies A Case Study: Central Supply, Srinagarind Hospital, Faculty of Medicine Khon Kaen University - Supanputta, Apiwat; Saenchaiyathon, Krittapha (NEU ACADEMIC AND RESEARCH JOURNAL, 2022)
A Model of Transportation of Sterile Medical Supplies: A Case study; Central supply, Srinagarind hospital, Faculty of Medicine, Khon Kaen University. The objective is to study the process of transportation of the central supply and to establish guidelines of the efficient transportation of the central supply. The instruments were the semi-structured interviews. During 2018-2019, the inventory level of the central supply unit has increased by 6% due to the growth of work. The manual trolley operation process is implementing two times per day for distributing and supplying the medical equipment to other departments. This supply model is carrying 6 boxes (60 litters capacity) at each delivery time. The transportation distance is 1300 meters max and 500 meters or 15 min and 10 seconds, 8 min and 12 seconds, respectively. The department has executed the “Health Object” (HO) software to enhance the medical equipment-tracking system. The health object practice is working through the barcode searching, medical expiry date and reclaim process. The findings of this study were; transportation, delaying in the sorting process, wasting of work process, and waiting time of the production process and transportation overlapping. The effective model of transportation of sterile medical supplies was created to enhance the transportation routes and congestion and to shorten the transportation time by 2 minutes. The health object information technology was implemented to decrease the time wasting of work process, and transport tacking. This technology was improved the speed of transportation and working process effectively.